The world book encyclopedia dictionary - Barnhart, Clarence L.(Editor in Chief); Illustrations, B/W. ([S.l.] : A Thorndike-Barnhart Dictionary Published for Field Enterprises Educational Corporation, 1963)
2 Big nice book in nice condition. .has all pages little wear and tear, but nothing major, still in very great reading condition. , no writing on the book pages. pictures are available.